ON THE OPTIMUM BUOYANCY WEIGHT RELATION FOR A BOTTOM TRAWL. - NARAYANAPPA, G; SATYANARAYANA, A V.V (Fishery Technology, 2016)
Comparative fishing operations were carried out with 0.55;0.75 and 1.00 buoyancy-weight relations of bottom trawl in orderto find out the optimum relation. Two nets Viz, 18.26 m. (60')two seam nylon and 16.16 m. (23') two seam cotton trawls wereused for the experiment. The results showed that the total catchper trawling hour with 0.75 B-W relation was 16.5% and 32.08%more than that with 0.55 and 1.00 B-W relation for nylon netused. A similar trend was noticed with cotton trawl also as thecatch rate with 0.75 B-W relation was 13.89% and 25.78% morethan that with 0.55 and 1.00 B-W relation. However, the analysisof catch composition indicated that the off bottom fishes like lactarius,upenoides sp., synagris sp. etc., were of more percentagewith 1.00 B-W relation, near bottom fish like saurida, sciaenidsetc., were more with 0.75 B-W relation, while the bottom fisheslike soles, prawns, skate3 and rays etc., were more with 0.55 B-Wrelation.